KEWENANGAN SYAHBANDAR DALAM PROSES BONGKAR MUAT BARANG DI PELABUHAN SAMARINDA - LOLO, SERLINA BUTTU (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe purpose of this study is to find out how the Responsibility of Shahbandar in the Security and Safety of Shipping and how the Duty of the Shahbandar in the Context of Improving the Security and Safety of Shipping. Based on the use of library research methods it is concluded that: 1. The responsibility of the harbor officers is very important because the security and safety of shipping is their duty. The actions he takes are / in order to improve security and safety supervision of matters relating to shipping. 2. The supervisory duties performed by a shahbandar in the context of regulating the facilities and infrastructure for the implementation of sea transportation operations are very important. A Syah Bandar in his duty must also ensure the awareness of sea transportation service users such as companies, ship owners, ship crews to obey the laws and statutory provisions that apply in the field of shipping safety which are generally still low.